Why we vaccinate incarcerated people first - J. Edward Berk; Josiah D. Rich; Lauren Brinkley‐Rubinstein (2021)
Few settings have been as dramatically affected by the COVID-19 pandemic as jails and prisons across the United States. The majority of the largest national outbreaks of COVID-19 have taken place in carceral facilities with some reporting positive testing rates of over 70%, [[1]Macmadu A. Berk J. Kaplowitz E. Mercedes M. Rich J.D. Brinkley-Rubinstein L COVID-19 and mass incarceration: a call for urgent action.Lancet Public Health. 2020; 5: e571-e572Summary Full Text Full Text PDF PubMed Scopus (24) Google Scholar]. The FDA has granted emergency use authorization for two SARS-CoV-2 vaccines that demonstrate near 95% efficiency, offering a life-saving tool to prevent future infections and outbreaks. Vaccine allocation, particularly among incarcerated individuals, remains a controversial topic. Yet there are very clear reasons why incarcerated people should be prioritized for vaccination efforts. First, incarcerated individuals are at high risk for Covid-19 transmission and severe disease. Congregate living settings, including jails and prisons, facilitate rapid spread of infection. Those in jails and prisons have a 5-fold greater likelihood of infection and 3-fold greater likelihood of death from Covid-19, [[2]Saloner B. Parish K. Ward J.A. Dilaura G. Dolovich S. COVID-19 cases and deaths in federal and state prisons.JAMA - J Am Med Assoc. 2020; 324: 602-603Crossref PubMed Scopus (218) Google Scholar]. Vaccine allocation should follow the epidemiology and be deployed in settings that will have the most impact: where there have been the most cases and more severe disease. Jails and prisons certainly meet these criteria. Second, jails bring large numbers of individuals into these high-risk spaces and then release them back to the community where the virus can spread to others. Mass incarceration has resulted in nearly 11 million people cycling through the system in any given year, mostly for short-term stays. And, no jail is an island: correctional officers, lawyers, physicians, social workers, dentists, and other staff go in and out of these facilities and ultimately go home to their families in neighboring communities. High rates of infection in a jail can lead to high rates of infection in a community. Indeed, during the first wave of Covid-19 infection, an estimated 16% of state-wide Covid-19 infections were linked to Chicago's Cook County jail alone, [[3]Reinhart E. Chen D.L. Incarceration And Its disseminations: COVID-19 pandemic lessons from Chicago's cook county jail.Health Aff (Millwood). 2020; 39: 1412-1418Crossref PubMed Scopus (109) Google Scholar]. Vaccinating people in jails can serve as an essential part of a multi-pronged public health strategy. Third, vaccinating incarcerated people can have a substantial impact on Black, Indigenous, and People of Color (BIPOC) communities that have suffered a greater health burden from the pandemic, [[4]Dyer O. Covid-19: black people and other minorities are hardest hit in US.BMJ. 2020; 369: m1483Crossref PubMed Scopus (152) Google Scholar]. Correctional facilities have a disproportionate makeup of these minority groups. High rates of carceral exposure in BIPOC communities further exacerbated COVID-19-related racial disparities, [[5]Lopez L. Hart L.H. Katz M.H. Racial and ethnic health disparities related to COVID-19.JAMA - J Am Med Assoc. 2021; 325: 719Crossref PubMed Scopus (350) Google Scholar]. Moreover, people who have been incarcerated and people who live in communities with a disproportionate burden of incarceration often face other barriers to healthcare access. Many advocates have appropriately argued for vaccine allocation to be equitable. To ensure health equity in vaccine allocation, jails offer a target approach to focus delivery to people of color, of low socioeconomic status, and to marginalized populations that otherwise may not have access to vaccine but suffer a disproportionate burden of disease. Fourth, vaccinating incarcerated individuals can potentially reduce municipal costs. Most correctional facilities are unable to offer acute level of health care to individuals who become sick and require hospitalization. Covid-19 complications ultimately burden neighboring health systems and hospitals in the area. These costs are ultimately passed on to taxpayers. Preventive vaccination can offer a possible reduction in local or state-level health care expenditures. Fifth, criminal justice facilities offer one of the most efficient ways to deliver vaccine to a population that has unparalleled accessibility. Many states struggle to efficiently deliver "shots in arms" and have reported backlogs of vaccines that go unused. Jails and prison system, by design, allow easy accessibility to the targeted population. Furthermore, there is some evidence that a substantial proportion of incarcerated people will agree to SARS-CoV-2 vaccination, [[6]Berk J., Murphy M., Kane K., Chan P., Rich J., Brinkley-Rubinstein L. SARS-CoV-2 Vaccination Uptake in a Correctional Setting. Submitted 2021.Google Scholar]. Sixth, there is a constitutional duty to provide appropriate health care to those in jail and prison. In the 1976 Supreme Court Case, Estelle vs. Gamble, a "deliberate indifference" to the health needs of those incarcerated is a cruel and unusual punishment and thus a violation of the Eight Amendment. Indeed, a federal court in the state of Oregon ruled incarcerated individuals had a constitutional right to vaccine and required prompt distribution to this population, [[7]Turcotte M. Sherman R. Norma D. Federal judge orders oregon state prisons to vaccinate inmates. New York Times, 2021https://www.nytimes.com/2021/02/03/world/oregon-prison-inmates-vaccine.htmlGoogle Scholar]. Seventh, the government has a moral responsibility to provide care to those under the custody of a department of corrections. Their criminal status should not play a role in deciding if they are "worthy" of receiving life-saving care. An individual's sentence was dictated in a court room and did not include contingencies for a global pandemic. It is for these reasons that the National Academy of Medicine, the American Medical Association, and a consortium of 7 academic institutions have voiced support for the prioritization of this often-overlooked population, [[8]Wang E. Brinkley-Rubinstein L. Puglisi L. Western B. Recommendations for prioritization and distribution of COVID-19 vaccine in prisons and jails. Columbia Justice Lab, 2020https://justicelab.columbia.edu/sites/default/files/content/COVID_Vaccine_White_Paper.pdfGoogle Scholar]. By prioritizing incarcerated people, policymakers can target a high-risk group, decrease community spread, improve equitable allocation, reduce community health system costs, ensure efficient delivery, and align allocation goals with the constitutional and moral duty to care for patients under the government's custody. Certainly, access to vaccine should be available to all as quickly as possible. And while other high-risk groups warrant similar consideration for prioritization, jails and prisons offer a smart public healthy strategy that may otherwise be ignored due to the stigma faced by this marginalized population. JR reports receiving grant funding from NIH, NIAID, CFAR Grant # P30AI042853 and NIH, NIGMS COBRE Grant #P20GM125507. The other authors have no financial disclosures or conflicts of interest.